2014
DOI: 10.1007/s12013-014-0331-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Protective Effect of Silibinin in Rats with Liver Damage Caused by Itraconazole

Abstract: Itraconazole (ITZ) belongs to the triazole group of antifungals with potent keratinophilic and lipophilic features. Hepatotoxicity is one of its most remarkable features. Silibinin (SIL) is a plant used worldwide which is used in the treatment of many liver diseases and it is especially very well known for its hepatoprotective-cytoprotective effect. The aim of our study was to research the protective effect of SIL in ITZ-induced hepatotoxicity using biochemical and pathological tests. Liver enzymes and antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…The oxidative stress damage caused by itraconazole is consistent with previous studies using different antifungals (Liu et al, 2002;Rodriguez and Buckholz, 2003;Amin and Hamza, 2005;Amin, 2008). Sozen et al (2014) found that the use of itraconazole increased oxidative stress through significant increases of myeloperoxidase and nitric oxide levels and significant decreases in the antioxidant activity of superoxide dismutase and GSH-peroxidase.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The oxidative stress damage caused by itraconazole is consistent with previous studies using different antifungals (Liu et al, 2002;Rodriguez and Buckholz, 2003;Amin and Hamza, 2005;Amin, 2008). Sozen et al (2014) found that the use of itraconazole increased oxidative stress through significant increases of myeloperoxidase and nitric oxide levels and significant decreases in the antioxidant activity of superoxide dismutase and GSH-peroxidase.…”
Section: Discussionsupporting
confidence: 89%
“…Treatment with the high dose (100 mg itraconazole/kg per day) induced bile duct hyperplasia, biliary cirrhosis, focal necrosis, and severe infiltration of neutrophils with detection of giant cells. Sozen et al (2014) found that itraconazole led to significant hepatocyte degeneration, bile duct hyperplasia, formation of bile duct plugs, inflammation of the portal/periportal area, and the presence of apoptotic cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Wolf extract through regulating arginine and proline metabolism, primary bile acid biosynthesis, and sphingolipid metabolism (Gao et al., ). In addition, silibinin showed the ability of enhancing antioxidant enzyme activities and preventing ROS formation, when administrated to the rats suffering from liver injury caused by itraconazole, a medication for fungal infections (Sozen et al., ).…”
Section: Protective Effects Of Natural Products On Drug‐induced Livermentioning
confidence: 99%